2013
DOI: 10.1111/1365-2745.12080
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐oxidative stress markers reveal absence of physiological deterioration with ageing in Borderea pyrenaica, an extraordinarily long‐lived herb

Abstract: Summary 1.In animals, age-associated disorders are believed to be connected to shifts in the antioxidant/prooxidant balance in favour of oxidative stress. However, the contribution of oxidative stress to ageing in long-lived perennials has not been explored to date.2. Here, we tested age-and sex-related changes in several photo-oxidative stress markers in Borderea pyrenaica, a small dioecious geophyte relict of the Tertiary with one of the longest life spans ever recorded for a non-clonal herb (more than 300 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…This was not observed here in either studied population. Small sizes throughout their lifespan, as it happens in perennial herbs (García et al, 2011;Morales et al, 2013;, may protect S. longifolia plants from the potential negative effects of aging. It appears, therefore, that whole-plant senescence in this species may be attributed to reproduction and extrinsic factors, such as drought stress, but not to ageing, as only very small individuals (, 30 mm diameter) die more frequently in the two lowest populations.…”
Section: Non-clonal Clonalmentioning
confidence: 99%
“…This was not observed here in either studied population. Small sizes throughout their lifespan, as it happens in perennial herbs (García et al, 2011;Morales et al, 2013;, may protect S. longifolia plants from the potential negative effects of aging. It appears, therefore, that whole-plant senescence in this species may be attributed to reproduction and extrinsic factors, such as drought stress, but not to ageing, as only very small individuals (, 30 mm diameter) die more frequently in the two lowest populations.…”
Section: Non-clonal Clonalmentioning
confidence: 99%
“…1). Interestingly, fecundity of this species increases with aging, representing a case of negative senescence (Garcia et al, 2011;Morales et al, 2013). If mortality falls as size increases and if size increases with age, then mortality will fall with age, and negative senescence occurs (Vaupel et al, 2004).…”
mentioning
confidence: 99%
“…The plant literature is indeed not exception to ecological examples of how propagation and modular partitioning may slow down or even reset the biological watch. The herbaceous perennial plant Borderea pyrenaica does not show any signs of physiological (Morales et al 2013) or demographic (García et al 2011) deterioration with age; in this case, the species is known to have a highly modular design in its shoot apical meristem arrangement (García et al 2011). Similarly, recently, Mencuccini et al (2013) have shown a lack of physiological decline in Scots pine (Pinus sylvestris) module performance grafted onto older genets.…”
Section: Discussionmentioning
confidence: 99%